Impact of Disease on Plasma and Lung Exposure of Chloroquine, Hydroxychloroquine and Azithromycin: Application of PBPK Modeling. Issue 5 (16th July 2020) - Rowland Yeo, Karen; Zhang, Mian; Pan, Xian; Ban Ke, Alice; Jones, Hannah M.; Wesche, David; Almond, Lisa M.
Abstract : We use a mechanistic lung model to demonstrate that accumulation of chloroquine (CQ), hydroxychloroquine (HCQ), and azithromycin (AZ) in the lungs is sensitive to changes in lung pH, a parameter that can be affected in patients with coronavirus disease 2019 (COVID‐19). A reduction in pH from 6.7 to 6 in the lungs, as observed in respiratory disease, led to 20‐fold, 4.0‐fold, and 2.7‐fold increases in lung exposure of CQ, HCQ, and AZ, respectively. Simulations indicated that the relatively high concentrations of CQ and HCQ in lung tissue were sustained long after administration of the drugs had stopped. Patients with COVID‐19 often present with kidney failure. Our simulations indicate that renal impairment (plus lung pH reduction) caused 30‐fold, 8.0‐fold, and 3.4‐fold increases in lung exposures for CQ, HCQ, and AZ, respectively, with relatively small accompanying increases (20 to 30%) in systemic exposure. Although a number of different dosage regimens were assessed, the purpose of our study was not to provide recommendations for a dosing strategy, but to demonstrate the utility of a physiologically‐based pharmacokinetic modeling approach to estimate lung concentrations. This, used in conjunction with robust in vitro and clinical data, can help in the assessment of COVID‐19 therapeutics going forward.